Characteristics of Effective Self-Regulated Learning Interventions in Mathematics Classrooms: A Systematic Review - Wang, Ying; Sperling, Rayne A. (Frontiers in Education, 2020)
Several meta-analyses suggest that identifiable characteristics of self-regulated learning interventions result in improvement in students’ academic performance and self-regulatory competence across content areas. Nevertheless, little is known about recent interventions and about specific characteristics of interventions that may be domain-specific. In this systematic review, we targeted mathematics and reviewed 36 self-regulated learning intervention studies conducted with school-aged learners. We examined patterns of effective interventions with identified characteristics, such as theoretical guidance, type of strategies instructed, type of outcome assessments, and targeted outcomes. Findings revealed that those interventions grounded in metacognition-oriented theories and those interventions that targeted multiple strategies including cognitive, metacognitive, and motivational, tended to yield effective increases in both mathematics achievement and self-regulated learning. The review also examined patterns within interventions conducted from 1992 – 2020. Findings indicate recent interventions tend to adopt a social-cognitive SRL model and employ standardized knowledge assessments. Implications for practice and future self-regulated learning interventions in mathematics are discussed.